Pengaruh Deforestasi Dan Tingkat Kebakaran Hutan Terhadap Tingkat Emisi Gas Rumah Kaca - Sri Maryani (Bumi Lestari Journal of Environment, 2020)
This study aims to determine the effect of the area of Forest Fire and Deforestation Figures on Green House Gas Emission Level. This study uses descriptive quantitative research, with statistical analytical methods. The data source is processed with the Importance-Performance Analysis, so that the area can be used as a reference in reducing the level of greenhouse gas emissions. The provinces of South Kalimantan, South Sumatra and Papua are areas prone to fires which are suspected not to be affected by the high level of Indonesia's deforestation within and outside the Forest Zone, but there may be other factors that play a role in the emergence of the forest fires. It is suspected that among the factors that can be a trigger factor for high levels of forest fires that are directly related to the increase in the number of greenhouse gas emissions, namely the distribution of the peat deposits.